Understanding and avoiding late presentation for HIV diagnosis – study protocol of a trial using mixed methods (FindHIV). Issue 12 (2nd December 2021) - Valbert, Frederik; Wolf, Eva; Preis, Stefan; Schellberg, Sven; Schewe, Knud; Hanhoff, Nikola; Mück, Birgit; Kögl, Christine; Lauscher, Paul; Wasem, Jürgen; Neusser, Silke; Neumann, Anja
ABSTRACT: Many patients infected with HIV are diagnosed at an advanced stage of illness. These late presenters are individuals with a CD4 cell count of less than 350 cells/µL and/or an AIDS defining disease at initial HIV diagnosis. Purpose of FindHIV is to develop and distribute a questionnaire/scoring system aimed at a reduction in late presentation. FindHIV uses a mixed methods approach. In a first step, primary data of patients were collected. Inclusion criteria were: age ≥ 18 years, cognitive ability and language skills to participate in the study, initial HIV diagnosis within the past 6 months, and patient informed consent. Descriptive methods and regression models are used to identify: (1) patient characteristics associated with late presentation and (2) contacts to the healthcare system with indicator diseases that did not lead to HIV testing. Secondly, a questionnaire/scoring system is created by an expert panel. Afterwards the questionnaire/scoring system is to be disseminated. The greatest challenge was in reaching an adequate sample size. Another risk may be a recall bias. Nevertheless, FindHIV is devised as an in-depth study of the phenomenon of late presentation with potential to significantly improve HIV detection.